Effects of compression running pants and treadmill running stages on knee proprioception and fatigue-related physiological responses in half-marathon runners - Chang, L.; Fu, S.; Li, J.; Wu, S.; Adams, R.; Han, J.; Han, C. (Frontiers in Physiology, 2022)
Background: Knee injury is common in half-marathon runners, however, the effect of compression running pants on fatigue and knee proprioception remains unclear.